Centrifugally Spun SnO2 Microfibers Composed of Interconnected Nanoparticles as the Anode in Sodium‐Ion Batteries. Issue 12 (19th October 2015) - Lu, Yao; Yanilmaz, Meltem; Chen, Chen; Dirican, Mahmut; Ge, Yeqian; Zhu, Jiadeng; Zhang, Xiangwu
Abstract: SnO2 microfibers were synthesized by using centrifugal spinning technology and were evaluated as the anode in sodium‐ion batteries. The as‐prepared SnO2 microfibers are composed of interconnected nanoparticles with small interparticle openings. The 1‐demensional fibrous morphology, fine particle size, and open pore structure result in reduced electrochemical impedance and enhanced electrochemical performance. The highest capacity achieved is 567 mAh g −1 at 20 mA g −1 . At a much higher current density of 640 mA g −1, the microfiber electrode still retains a high capacity of 158 mAh g −1 after 50 cycles. The SnO2 microfibers also demonstrate good rate performance in a current range of 20–640 mA g −1 . The results demonstrate that SnO2 microfibers are a potential anode material candidate for sodium‐ion batteries and that centrifugal spinning offers a feasible solution for the large‐scale production of fibrous electrode materials. Abstract : Spin for energy : A rapid and scalable centrifugal spinning technology is developed to prepare SnO2 microfibers. The as‐prepared SnO2 microfibers are composed of interconnected nanoparticles and exhibit enhanced electrochemical performance compared to their particle rival.